Increased mitochondrial apoptotic priming with targeted therapy predicts clinical response to re‐induction chemotherapy. Issue 3 (22nd December 2019) - Garcia, Jacqueline S.; Bhatt, Shruti; Fell, Geoffrey; Sperling, Adam S.; Burgess, Michael; Keshishian, Hasmik; Yilma, Binyam; Brunner, Andrew; Neuberg, Donna; Carr, Steven A.; Ebert, Benjamin L.; Ballen, Karen; et al.
Abstract: Most patients with relapsed or refractory (R/R) acute myeloid leukemia (AML) do not benefit from current re‐induction or approved targeted therapies. In the absence of targetable genetic mutations, there is minimal guidance on optimal treatment selection particularly in the R/R setting highlighting an unmet need for clinically useful functional biomarkers. Blood and bone marrow samples from patients treated on two clinical trials were used to test the combination of lenalidomide (LEN) and MEC (mitoxantrone, etoposide, and cytarabine) chemotherapy in R/R AML patients. The bone marrow samples were available to test the clinical utility of the mitochondrial apoptotic BH3 and dynamic BH3 profiling (DBP) assays in predicting response, as there was no clear genetic biomarker identifying responders. To test whether LEN‐induced mitochondrial priming predicted clinical response to LEN‐MEC therapy, we performed DBP on patient myeloblasts. We found that short‐term ex vivo treatment with lenalidomide discriminated clinical responders from non‐responders based on drug‐induced change in priming (delta priming). Using paired patient samples collected before and after clinical LEN treatment (prior to MEC dosing), we confirmed LEN‐induced increased apoptotic priming in vivo, suggesting LEN enhanced vulnerability of myeloblasts to cytotoxic MEC chemotherapy. This is the first study demonstrating the potential role of DBP in predicting clinical response to a combination regimen. Our findings demonstrate that functional properties of relapsed AML can identify active therapies.